(untitled) (Al-Farooq Journal of Sciences, 2026)
: This study seeks to explain the escalating great-power competition among the United States, Russia, and China for influence in the Mediterranean basin, and its implications for the settlement of the Libyan crisis after 2011. It draws on security dilemma theory from its classical formulation by Butterfield, Herz, and Jervis, through Tang’s critical reformulation (Tang, 2009), to its contemporary applied extension by Walt (Walt, 2022). The study posits that the intensifying military and economic presence of these three powers does not necessarily reflect mutual aggressive intent, but rather stems from a structural logic imposed by international anarchy, and that the sources of the resulting strategic ambiguity vary according to each actor’s distinctive pattern of behavior: a gap between official discourse and actual conduct in Washington’s case; Moscow’s compelled adoption of a "second-front" logic following the loss of its Tartus base; and Beijing’s "cumulative institutional-economic penetration," which resists straightforward classification. Adopting a descriptive-analytical method and drawing on verified primary strategic documents, recent peer-reviewed literature, and specialized think-tank reports, the study concludes that the Libyan crisis has become a testing ground for the realignment of the balance of power in the southern Mediterranean, and that the security dilemma among these powers is sustained primarily by multi-sourced strategic uncertainty over intentions rather than by a necessarily irreconcilable conflict of objectives.